(untitled) (The Review of Diabetic Studies, 2025)
Corporate Wellness Initiatives (CWIs) have emerged as a critical strategy for enhancing employee well-being and organisational efficiency in knowledge-intensive industries such as Information Technology (IT). This paper investigates the influence of CWIs on workforce morale and productivity, focusing on how mental health, fitness, and flexible work programs contribute to employee engagement and performance. Drawing from organisational psychology theories such as Herzberg’s Two-Factor Theory, Job Characteristics Theory, and the Conservation of Resources (COR) framework, this study employs a mixed-methods approach integrating surveys, performance metrics, and semi-structured interviews. The findings reveal that well-structured CWIs significantly enhance morale, reduce absenteeism, and improve overall productivity. The study also highlights that management commitment, organisational culture, and continuous evaluation play pivotal roles in ensuring the sustainability and effectiveness of wellness programs.